PRIORITIES IN THE USE OF INNOVATIVE TECHNOLOGIES IN THE PRODUCTION OF BUILDING MATERIALS AND RELATED SOLUTIONS - Q. R. Kholmirzayev (Journals Park Publishing, 2023)
The article examines the prospects for the development of material resource management in construction using modern information technologies and digital tools. The analysis showed that existing methods of managing material resources have their advantages and disadvantages, but their effectiveness can be improved by using modern information technologies and digital tools for project and resource management. However, for this it is necessary to develop and implement appropriate regulatory documents and train construction company personnel to use new tools for managing material resources.
Keywords: management, material resources, construction industry, just-in-time, inventory management, information technology, digital tools, regulatory framework, efficiency, project management, cost optimization.